Non-Hodgkin lymphoma and pre-existing conditions: spectrum, clinical characteristics and outcome in 213 children and adolescents - Attarbaschi, Andishe; Carraro, Elisa; Abla, Oussama; Barzilai-Birenboim, Shlomit; Bomken, Simon; Brugieres, Laurence; Bubanska, Eva; Burkhardt, Birgit; Chiang, Alan K S; Csoka, Monika; Fedorova, Alina; Jazbec, Janez; et al. (Haematologica, 2016)
Children and adolescents with pre-existing conditions such as DNA repair defects or other primary immunodeficiencies have an increased risk of non-Hodgkin lymphoma. However, large-scale data on patients with non-Hodgkin lymphoma and their entire spectrum of pre-existing conditions are scarce. A retrospective multinational study was conducted by means of questionnaires sent out to the national study groups or centers, by the two largest consortia in childhood non-Hodgkin lymphoma, the European Intergroup for Childhood non-Hodgkin Lymphoma, and the international Berlin-Frankfurt-Münster Study Group. The study identified 213 patients with non-Hodgkin lymphoma and a pre-existing condition. Four subcategories were established: a) cancer predisposition syndromes (n=124, 58%); b) primary immunodeficiencies not further specified (n=27, 13%); c) genetic diseases with no increased cancer risk (n=40, 19%); and d) non-classifiable conditions (n=22, 10%). Seventy-nine of 124 (64%) cancer predispositions were reported in groups with more than 20 patients: ataxia telangiectasia (n=32), Nijmegen breakage syndrome (n=26), constitutional mismatch repair deficiency (n=21). For the 151 patients with a known cancer risk, 5-year event-free survival and overall survival rates were 40%±4% and 51%±4%, respectively. Five-year cumulative incidences of progression/relapse and treatment-related death as a first event were 22%±4% and 24%±4%, respectively. Ten-year incidence of second malignancy was 24%±5% and 7-year overall survival of the 21 patients with a second malignancy was 41%±11%. Patients with non-Hodgkin lymphoma and pre-existing conditions have an inferior survival rate with a large proportion of therapy-related deaths compared to patients with non-Hodgkin lymphoma and no pre-existing conditions. They may require special vigilance when receiving standard or modified/reduced-intensity chemotherapy or when undergoing allogeneic stem cell transplantation.
Keywords: Disease Progression; komorbidita; kojenec; progrese nemoci; mladiství; výsledek terapie; náchylnost k nemoci; Kaplan-Meier Estimate; mužské pohlaví; ochrana veřejného zdraví; Kaplanův-Meierův odhad; Infant; Public Health Surveillance; recidiva; kombinovaná terapie; dítě; Child; Infant, Newborn; Child, Preschool; ženské pohlaví; novorozenec; Humans; předškolní dítě; sekundární malignity; Recurrence; Comorbidity; Disease Susceptibility; Combined Modality Therapy; nehodgkinský lymfom; Lymphoma, Non-Hodgkin; Female; Adolescent; Treatment Outcome; lidé; Male; Neoplasms, Second Primary